Impact of asthma on linear growth in preschool children: a cross-sectional study in Iraq (Journal of Ideas in Health, 2025)
Background: Asthma is a common chronic respiratory condition in children, often emerging during the preschool years. Its long-term effects may extend beyond respiratory health, potentially influencing physical development, including linear growth. This study aims to determine whether a significant association exists between asthma and impaired linear growth of preschool-aged children in Iraq.Methods: A cross-sectional study was conducted between 1st January and 30th June 2024 at Al-Batool Teaching Hospital, pediatric outpatient clinics, Diyala, Iraq. The cohort analyzed data of 90 children aged 1–5 years who has been divided into two groups: asthmatic (n=45) and non-asthmatic controls (n=45). Height-for-age z-scores (HAZ) were used to assess linear growth. Data were collected through caregiver interviews and medical record reviews, including sociodemographic characteristics and clinical information. Chi-square and logistic regression analyses were employed to identify significant associations between asthma and stunting.Results: Among asthmatic children, 42.2% had low HAZ scores compared to 20.0% of non-asthmatic children (p=0.03). Logistic regression showed that asthma was significantly associated with linear growth impairment (OR = 2.8, 95% CI: 1.1–7.2, p=0.028), even after adjusting for confounders such as nutrition and parental education.Conclusion: Asthma in preschool children is significantly associated with impaired linear growth. Early detection, asthma control, and integrated nutrition strategies are crucial to improving both respiratory and growth outcomes. Further longitudinal studies are needed to explore causality and long-term developmental impacts.
Keywords: Asthma, Linear Growth, Stunting, Preschool Children, Iraq, Height-For-Age Z-Score, Childhood Morbidity, Iraq